Microencapsulation of hydrosoluble extract of babassu nut press cake - Pãmella Fronza; Robson dos Santos Barbosa; Thiago Silva Novais; Erlane da Rocha Fernandes; Fabiana de Oliveira Pereira; Abraham Damian Giraldo Zuniga (Semina: Ciências Agrárias, 2020)
Orbignya phalerata Mart. has great socio-economic value, originating various products and by-products; however, there are few studies about obtaining food products from of this raw material. In face of that reality, this study aimed to obtain powder extract from press cake of the babassu nut kernel, and to verify the influence of varying concentrations of Maltogill®10 and drying temperature on process yield through a factorial design, as well as to characterize the final product. Babassu nut used for pressing and acquisition of residual press cake and extract. Spray dryer was used to obtain the powder extract, which adopted a rotating central composite design (RCCD with 11 trials). The final product was characterized by analyses of moisture, solubility, hygroscopicity, water activity and bulk density. The experimental design showed significant influence (p ? 0.05) for the variables inlet temperature in the linear and quadratic models, focusing only on the linear term and the interaction between them, the model adjusted in planning was considered predictive; the best productivity obtained (80.37%), was for the temperature of 95°C with encapsulating agent of 18%. With respect to the powder product analysis, low moisture values, hygroscopicity, and density were observed, as solubility and water activity within the recommended parameters.